2022
DOI: 10.1093/brain/awac236
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Wnt/β-catenin pathway mitigates blood–brain barrier dysfunction in Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder that causes age-dependent neurological and cognitive declines. The treatments for AD pose a significant challenge, because the mechanisms of disease are not being fully understood. Malfunction of the blood-brain barrier (BBB) is increasingly recognized as a major contributor to the pathophysiology of AD, especially at the early stages of the disease. However, the underlying mechanisms remain poorly characterized, while few molecules can directly target a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 75 publications
8
39
0
Order By: Relevance
“…This would be similar to a recent report showing CRISPR-Cas9 GLUT1 truncation decreased BMEC bioenergetics and negatively impacted neuro angiogenesis (Pervaiz et al, 2022). Expression of claudin-5, the dominant tight junction protein in the BBB, has been shown to decrease in parallel with GLUT1 following suppression of the Wnt/β-catenin pathway (Wang et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This would be similar to a recent report showing CRISPR-Cas9 GLUT1 truncation decreased BMEC bioenergetics and negatively impacted neuro angiogenesis (Pervaiz et al, 2022). Expression of claudin-5, the dominant tight junction protein in the BBB, has been shown to decrease in parallel with GLUT1 following suppression of the Wnt/β-catenin pathway (Wang et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…This would be similar to a recent report showing CRISPR-Cas9 GLUT1 truncation decreased BMEC bioenergetics and negatively impacted neuro angiogenesis (Pervaiz et al, 2022). Expression of claudin-5, the dominant tight junction protein in the BBB, has been shown to decrease in parallel with GLUT1 following suppression of the Wnt/β-catenin pathway (Wang et al, 2022). Our previous research has demonstrated that CMV infection dysregulates this pathway (Angelova et al, 2012; Zwezdaryk et al, 2016) providing a possible mechanism for these changes.…”
Section: Discussionmentioning
confidence: 99%
“…By linking white matter injury to cholesterol and Abeta metabolism and transport, we postulate that this helps explain why so many systemic factors increase the risk of AD. We postulate that the many AD risk factors act on white matter particularly with aging when the BBB is leakier (Methia et al, 2001;Ujiie et al, 2003;Zipser et al, 2007;Zlokovic, 2008;Deane et al, 2009;Farrall and Wardlaw, 2009;Jaeger et al, 2009;Lamartinière et al, 2018;Ma et al, 2018;Barisano et al, 2022;Wang et al, 2022c). Indeed, BBB dysfunction precedes amyloid plaque formation (Ujiie et al, 2003).…”
Section: Ad Animal Modelsmentioning
confidence: 99%
“…APOE deficiency compromises the BBB especially after injury, whereas APOE protects against neuropathology induced by high cholesterol diets and maintains the BBB during aging (Fullerton et al, 2001;Methia et al, 2001;Mulder et al, 2001). Abeta causes BBB dysfunction of vascular endothelial cells which is prevented by LRP6 activation of the Wnt/β-catenin pathways (Wang et al, 2022c).…”
Section: Blood Brain Barrier/pericytesmentioning
confidence: 99%
“…For instance, increased remnants of capillaries, namely string vessels, are damaged vessels after BEC destruction, which have been reported in the AD brain for a long time (Brown, 2010).In vitro, different aggregation properties and heterogeneous compositions of Aβ peptides have distinct effects on endothelial cell viability, BBB integrity, and angiogenesis (Parodi-Rullan et al, 2020). Additionally, Aβ suppressed Wnt/β-catenin signaling by activation of GSK3β both in vivo and in vitro (Wang et al, 2022). The maintenance of BBB is dependent on the β-catenin signaling in BECs (Tran et al, 2016).…”
Section: Alzheimer's Diseasementioning
confidence: 94%